Analisis Kritis Filsafat Pendidikan Agama Kristen Terhadap Isu Kristen Progresif - Simarmata, Paden Leonard; Siallagan, Thomson (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2024)
AbstractIn the Christian context, religious education serves as a foundation for ongoing spiritual understanding and practice. However, like any other field of education, Christian RE is constantly evolving and adapting to the dynamics of changing times. In the present day, progressive issues have become a major focus of theological debate and Christian religious education. Some problem formulations that could be used as a focus for research are: How does the philosophy of Christian religious education contained in the Acts of the Apostles respond to the issue of progressive Christianity; How can the theological concepts found in the Acts of the Apostles be contextually applied in the context of progressive Christian religious education? The purpose of this study is to analyse and understand the traditional understanding of the Christian religious teachings contained in the Book of Acts, and to produce insights and recommendations that can be used by educators. Philosophy of Christian education in the light of the Acts of the Apostles, progressive Christian issues, critical analysis of progressive Christianity based on the meaning of the term 'Christian' in the Acts of the Apostles. Keywords: philosophy of education, Christianity, progressive Christianity  AbstrakDalam konteks kekristenan, pendidikan agama berfungsi sebagai fondasi untuk pemahaman dan praktik spiritual yang berkelanjutan. Namun demikian, sama halnya dengan bidang pendidikan lainnya, pendidikan agama Kristen juga terus berkembang dan beradaptasi dengan dinamika perubahan zaman. Di era kontemporer, isu-isu progresif telah menjadi fokus yang signifikan dalam perdebatan teologis dan pendidikan agama Kristen. Beberapa rumusan masalah yang mungkin dapat dijadikan sebagai fokus penelitian yatiu, Bagaimana filsafat pendidikan agama Kristen yang terkandung dalam Kitab Kisah Para Rasul merespons isu kristen progresif, Bagaimana konsep-konsep teologis yang ditemukan dalam Kitab Kisah Para Rasul dapat diterapkan secara kontekstual dalam konteks pendidikan agama Kristen yang progresif? tujuan penelitian ini adalah menganalisis dan memahami pemahaman tradisional tentang ajaran agama Kristen yang terkandung dalam Kitab Kisah Para Rasul, menghasilkan wawasan dan rekomendasi yang dapat digunakan oleh pendidik. Filsafat Pendidikan Agama Kristen ditinjau dari Kisah Para Rasul, Isu Kristen Progresif, Analisis Kritis Terhadap Kristen Progresif Berdasarkan Makna Istilah “Kristen” dalam Kisah Para Rasul Kata Kunci: filsafat pendidikan, agama kristen, kristen progresif